Handgrip and Quadriceps Strength as Independent Predictors of Post-Stroke Depression and Anxiety - Adekola Ademoyegun; Adebukola Ibitoye; Chidozie Mbada; Oluwatobi Malomo; Omotola Adelowokan; Ishanosen Aghedo; Wasiu Rasaq; Bobola Adeoye; Mistura Olaoye (Journal of Rehabilitation Sciences and Research, 2022)
Background: The objective of this study was to whether handgrip andquadriceps strength can predict post-stroke depression (PSD) and post-strokeanxiety (PSA).Methods: This cross-sectional study involved sixty-six consenting strokepatients whose symptoms of depression and anxiety and affected handgrip andquadriceps strength were assessed by the Hospital Anxiety and Depression Scale(HADS) and handheld dynamometers. Data was analyzed using descriptive andinferential statistics. Alpha level was set at P<0.05.Results: The participants’ mean handgrip and quadriceps strength were 19.03kg and 20.70 kg, respectively, while the prevalence of PSD and PSA were 33.4%and 42.4%, respectively. PSD was significantly correlated with PSA (r=0.61;P<0.001), handgrip strength (r=-0.24; P=0.049), functional independence(r=-0.26; P=0.036), and stroke severity (r=0.26; P=0.039), while PSA wassignificantly correlated with stroke severity (r=0.25; P=0.046) and age (r=-0.25; P=0.048). Multiple linear regression results indicate that handgrip andquadriceps strength were not independent predictors of PSD and PSA (P>0.05);however, the presence of PSA was an independent predictor of PSD (B=0.590;P<0.001), while the presence of PSD (B=0.621; P=0.001) and younger age (B=-0.307; P<0.001) were independent predictors of PSA.Conclusion: Handgrip and quadriceps strength are not significant predictors ofPSD and PSA in stroke survivors; however, PSD and PSA can predict each other,indicating a bi-directional relationship, while age is a negative predictor of PSA.